Gianotti-Crosti syndrome, pityriasis rosea, asymmetrical periflexural exanthem, unilateral mediothoracic exanthem, eruptive pseudoangiomatosis and papular-purpuric gloves and socks syndrome: a brief review and arguments for diagnostic criteria - Antonio Chuh; Vijay Zawar; Michelle Law; Gabriel Sciallis (MDPI AG, 2012)
Several exanthems including Gianotti-Crosti syndrome, pityriasis rosea, asymmetrical periflexural exanthem, eruptive pseudoangiomatosis, and papular-purpuric gloves and socks syndrome are suspected to be caused by viruses. These viruses are potentially dangerous. Gianotti-Crosti syndrome is related to hepatitis B virus infection which is the commonest cause of hepatocellular carcinoma, and Epstein-Barr virus infection which is related to nasopharyngeal carcinoma. Pityriasis rosea has been suspected to be related to human herpesvirus 7 and 8 infections, with the significance of the former still largely unknown, and the latter being a known cause of Kaposi's sarcoma. Papular-purpuric gloves and socks syndrome is significantly associated with human B19 erythrovirus infection which can lead to aplastic anemia in individuals with congenital hemoglobinopathies, and when transmitted to pregnant women, can cause spontaneous abortions and congenital anomalies. With viral DNA sequence detection technologies, false positive results are common. We can no longer apply Koch's postulates to establish causeeffect relationships. Biological properties of some viruses including lifelong latent infection, asymptomatic shedding, and endogenous reactivation render virological results on various body tissues difficult to interpret. We might not be able to confirm or refute viral causes for these rashes in the near future. Owing to the relatively small number of patients, virological and epidemiology studies, and treatment trials usually recruit few study and control subjects. This leads to low statistical powers and thus results have little clinical significance.